ʼDzin pa raṅ grol gyi chos skor : the collected visionary teachings on the practice of the Gcod precepts - Ye-śes-rdo-rje, Mdo Mkhyen-brtse, 1800-1859? (D. G. Khochhen Trulku, 1975)
Teachings on Lamaist meditational practice of the Nyingmapa tradition.